Development of Community Enterprise Model 4.0, Food for Grassroot Economic: A Case Study of Swine Farmer in a Community Enterprise of Ban Ko Sathon, Tak Bai District, Narathiwat Province - Khongsen, Mongkon; Sakulrat, Benjaree; Palasai, Wasan; Kaewboon, Nattaphat (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2022)
This research is a mixed research study. The objectives of this research were 1) to develop a model of production and distribution process of community enterprise groups, 2) to develop a model of product packaging design for community enterprises, 3) to develop a model to increase the efficiency and effectiveness of the production process, and 4) to assess the satisfaction of the stakeholders. The qualitative data were collected by in-depth interview while the quantitative date were collected by questionnaire. The samples were 25 entrepreneurs of community enterprises, raising swine at Ban Ko Sathon, Tak Bai District, Narathiwat Province, selected by purposive sampling. Data were analyzed using content analysis for model development and using descriptive statistics for the stakeholders’ satisfaction. The results showed that 1) the major part in the development of production and distribution processes was the selection of meat, and the significant issues needed to be improved included 2 aspects: marketing, sales and technology development, 2) the development of packaging design should focus on vacuum bags and microwave-safe packaging, 3) the developed model to increase the efficiency and effectiveness of the production process should focus on demand-supply, cost saving, self-raised pigs, benefit sharing, beauty of product packaging, product guarantee, freshness and easy to cook, and 4) the result of the overall stakeholder satisfaction of the swine community enterprise group was at the highest level.